An Irish Benedictine Adventure: Dom Francis Sweetman (1872-1953) and Mount St Benedict, Gorey - Bellenger, Dominic Aidan (Studies in church history, 1989)
On 11 January 1913 the following article, signed by ‘Me Fein’, appeared in an Irish periodical of pronounced nationalist views under the heading ‘Wexford Again. More Language Compulsion’: Compulsion in educational matters seems to revolt some good souls in Wexford, and the following flash will possibly electrify Mr Fanning of the County Council of that model county. (By the way, it seems to be rapidly becoming the ‘model county’ for Irish Ireland wobbling and drunkenness prosecutions.) A school has been established at Gorey for some years by the Benedictine Fathers, for the better class young Irishmen, and it will be of interest to note some features of that educational establishment.